2020
DOI: 10.1186/s12891-020-03659-7
|View full text |Cite
|
Sign up to set email alerts
|

Large autologous ilium with periosteum for tibiotalar joint reconstruction in Rüedi-Allgöwer III or AO/OTA type C3 pilon fractures: a pilot study

Abstract: Background Management of Rüedi-Allgöwer III or AO/OTA type C3 pilon fracture presents numerous challenges to the orthopaedic surgeon. A joint preservation technique using a large autologous ilium with periosteum in combination with internal implant fixation was reported to improve the outcome of reconstruction. Methods Twenty-five patients according to Tscherne/Oestern FxCO-I closed fracture and FxOI open fractures classification aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…In recent years, there have been small reports of using osteoperiosteal autologous grafts to treat osteochondral lesions of the talus with surprisingly comparable results with osteochondral transplantation. 6,45,53 In 2020, Li et al 22 reported using large autologous ilium with periosteum to manage severe acute pilon fractures with favorable short-term results. In our clinical experience, however, such large regions of unreconstructable articular surfaces are rarely seen in acute injuries, and large autologous ilium with periosteum grafts may be unnecessary in the majority of fresh pilon fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been small reports of using osteoperiosteal autologous grafts to treat osteochondral lesions of the talus with surprisingly comparable results with osteochondral transplantation. 6,45,53 In 2020, Li et al 22 reported using large autologous ilium with periosteum to manage severe acute pilon fractures with favorable short-term results. In our clinical experience, however, such large regions of unreconstructable articular surfaces are rarely seen in acute injuries, and large autologous ilium with periosteum grafts may be unnecessary in the majority of fresh pilon fractures.…”
Section: Discussionmentioning
confidence: 99%